2021
DOI: 10.1108/apjml-05-2019-0321
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of consumer characteristics with respect to brand knowledge and product involvement on brand alliance evaluation

Abstract: PurposeThe purpose of this paper is to take the neglected influencing factors in brand alliance research into account based on consumer characteristics theory and discuss the influencing factors' interactive effects on brand alliance.Design/methodology/approachBased on the theory of consumer characteristics and the S&R model of brand alliance, an experimental design was conducted to examine the relationship among the various variables and moderators, which can test the changes of the dependent variables by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…They are also more confident and certain about their purchasing decisions (Alba and Wesley, 2000). In addition, the consumer behavior literature documents many moderating roles of consumer knowledge (Rao and Monroe, 1988;Cowley and Mitchell, 2003;Singh et al, 2021). For example, Zhan and He (2012) confirm the moderating effect of consumer knowledge on attitudes toward luxury brands; for more knowledgeable Chinese consumers, need for uniqueness shows a negative relationship with Consumer purchase intention of ICHP brand attitudes.…”
Section: Consumer Knowledgementioning
confidence: 92%
See 1 more Smart Citation
“…They are also more confident and certain about their purchasing decisions (Alba and Wesley, 2000). In addition, the consumer behavior literature documents many moderating roles of consumer knowledge (Rao and Monroe, 1988;Cowley and Mitchell, 2003;Singh et al, 2021). For example, Zhan and He (2012) confirm the moderating effect of consumer knowledge on attitudes toward luxury brands; for more knowledgeable Chinese consumers, need for uniqueness shows a negative relationship with Consumer purchase intention of ICHP brand attitudes.…”
Section: Consumer Knowledgementioning
confidence: 92%
“…They are also more confident and certain about their purchasing decisions (Alba and Wesley, 2000). In addition, the consumer behavior literature documents many moderating roles of consumer knowledge (Rao and Monroe, 1988; Cowley and Mitchell, 2003; Singh et al. , 2021).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…For example, Suh and Yi (2006) showed that less involved people present a stronger relationship between satisfaction and attitudes toward the brand than high involved consumers. Singh et al (2021) found contradictory results regarding the moderating role of product involvement in consumers’ perceptions of brand alliances. In the case of SBC – and although there are no conclusive results – Tran et al (2020) tested the moderating effect of product involvement in SBC relationships with personalized advertising and brand equity, while Fazli-Salehi et al (2022) studied the relationship of SBC and consumer traits and purchase intention, comparing high- and low-involvement products.…”
Section: Theoretical Background and Research Model Developmentmentioning
confidence: 98%
“…Further, extant literature has established the moderating role played by involvement between stimuli and consumers' responses (Krishnamurthy & Kumar, 2018; Singh et al, 2021). The results exhibited that highly involved consumers tend to show a robust behavioral response to the stimuli than low‐involved consumers.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%